Evaluation of Argentinean medicinal plants and isolation of their bioactive compounds as an alternative for the control of postharvest fruits phytopathogenic fungi - Di Liberto, Melina Gabriela (2019)
One of the main problems that fruit health goes through in recent years is the difficult eradication of their fungal pathogens after harvesting. This concern to the whole world because it represents huge losses of production, fruit export restrictions and consumers distrust. One of the alternatives to solve this problem could be the exploration of plants and their active compounds, which have proven to be antifungal against human pathogens, but now applied to the treatment of fruits health. In this work, eighteen plant species that grow in Argentina were evaluated against four phytopathogenic fungi that greatly affect the postharvest stage of fruits commercially important to our country. All the species studied were at least active against one fungus of the panel, while three of them displayed high antifungal properties inhibiting the growth of selected pathogens. In addition, bio-guided fractionation of these most active extracts, led to the isolation of some compounds which proved to be responsible for their antifungal activity. Although they are known compounds and were previously isolated from other natural sources, this is the first time that they are evaluated for their phytopathogenic activities against this panel of fungi.